Early Beringian Traditions: Functioning and Economy of the Stone Toolkit from Swan Point CZ4b, Alaska - Gauvrit Roux, Eugénie; Gómez Coutouly, Yan Axel; Holmes, Charles; Hirasawa, Yu (American Antiquity, 2024)
International audience Abstract The pressure knapping technique develops circa 25,000 cal BP in Northeast Asia and excels at producing highly standardized microblades. Microblade pressure knapping spreads throughout most of Northeast Asia up to the Russian Arctic, and Alaska, in areas where the human presence was unknown. Swan Point CZ4b is the earliest uncontested evidence of human occupation of Alaska, at around 14,000 cal BP. It yields a pressure microblade component produced with the Yubetsu method, which is widespread in Northeast Asia during the Late Glacial period. Through the techno-functional analysis of 634 lithic pieces from this site, this study seeks to identify the techno-economical purposes for which the Yubetsu method was implemented. Data show that the microblade production system is related to an economy based on the planning of future needs, which is visible through blanks standardization, their overproduction, their functional versatility, and the segmentation of part of the chaîne opératoire . This expresses the efficiency and economic value of the microblade production system. The flexible use of pressure microblades identified at Swan Point CZ4b is also found in Japan, Korea, Kamchatka, and the North Baikal region, suggesting that their modes of use accompany the spread of early microblade pressure knapping over an immense territory across Beringia. Les débitages par pression émergent ca. 25,000 cal BP au Nord-Est de l'Asie et permettent la confection de lamelles particulièrement standardisées, notamment au moyen de la méthode Yubetsu (i.e., débitage lamellaire à partir de préformes bifaciales). Ce bagage technique novateur accompagne le développement de l'occupation humaine en zone arctique et subarctique pendant le Dernier Maximum Glaciaire et le Tardiglaciaire et se retrouve dans la plupart de l'Asie du Nord-Est jusqu’à l'Arctique russe, et en Alaska. Swan Point CZ4b livre les plus anciennes industries connues en Alaska (ca. 14,000 cal BP) et c'est également le seul site d'Amérique ...